EFFECTIVENESS OF ILOPROST IN PATIENTS WITH PULMONARY HYPERTENSION FC III - IV BASED ON VORONEZH REGION REGISTRY DATA - O. M. Korolkova; T. M. Chernykh (Евразийский Кардиологический Журнал)
The purpose of the study: to study the effectiveness of the use of the drug iloprost in patients with PH III - IV FC according to the register of the Voronezh region. The material was the base register data. The effectiveness of the drug «iloprost» evaluated in patients with PH III - IV FC according to the register. The safety of therapy «iloprost» shown on the basis of a complex of clinical and hemodynamic parameters.Glinical example presented.